PRAGMATIC TRANSFER IN THE SPEECH ACT OF PROMISE AMONG STUDENTS - Benni Ichsanda Rahman (UIN Sumatera Utara, 2019)
The study is focused on investigating the English Department Students of Semarang State University perform the speech act of promise, the most dominant strategies used, the factors influence the students in performing promise, and to analyze the pragmatic transfer occurred in their English conversations. The respondents of this study were 25 students of the sixth semester English Department, Undergraduate Program, Semarang State University. The data were collected by Discourse Completion Task (DCT). The responses were classified into 13 promise strategies as proposed by Gibbs & Delaney (1987). Furthermore, their responses which contained the pragmatic transfer were also identified and interpreted into two types of pragmatic transfer based on Kasper (1992): pragma-linguistic transfer and socio-pragmatic transfer. Using the DCT, 245 responses in English and 168 responses in Bahasa Indonesia were collected. The result showed that the respondents dominantly used “explicit promise” strategy (26.53 %) in English illustration, and “future act” strategy (23.31 %) in Bahasa Indonesia illustration. Moreover, the most dominant factor that influenced promise performance was the social power level, followed by social distance, formality, and last rank of imposition. Last, there were pragmatic transfers occurred in performing the promise. The students still transferred their L1 cultural norms into English interactions specifically in making promise, both in pragma-linguistic transfer and socio-pragmatic transfer.